Problem: So I already know how to correctly find the formula for a Voigt model, but why is my proposed way incorrect? Equations and Assumptions: for dashpot: F = n(dx/dt), where n is the dashpot constant and dxdt is change in distance/change in time for spring: F = kx assuming: arm connecting dashpot and spring doesn't bend or rotate, then F applied is equal to Force on Spring + Force on Dashpot. Also, because the arm doesn't bend, displacement of Dashpot and Spring are equal. the correct equation: X = F(1-exp(-kt/n)) My Proposed Method: Force on spring + Force on dashpot = total Force (A) F + F = F kx + n(dx/dt) = F n(dx/dt) is Force on dashpot. why can't I separate to get: (ndx) = (Force on dashpot)dt then integrate to get, both from 0 to respective final values, to get (nx) = (Force on dashpot)(t) Then solve for Force on dashpot to get nx/t Then plug this in for Force on dashpot in equation (A) kx +nx/t = total Force Solve for X X = (F)/[(k+n)/t] Essentially, what I am asking is: why do I HAVE to leave the dx/dt in the dashpot equation as is? Why can I not just say F = n(dx/dt), then separate and integrate to get F = nx/t, and then just substitue this in equation (A)?